2016
DOI: 10.1016/j.celrep.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Microgliosis Due to Resident Microglial Proliferation Is Required for Pain Hypersensitivity after Peripheral Nerve Injury

Abstract: Summary Peripheral nerve injury causes neuropathic pain accompanied by remarkable microgliosis in the spinal cord dorsal horn. However, it is still debated whether infiltrated monocytes contribute to injury-induced expansion of the microglial population. Here we found that spinal microgliosis predominantly results from local proliferation of resident microglia but not from infiltrating monocytes after spinal nerve transection (SNT), using two genetic mouse models (CCR2RFP/+:CX3CR1GFP/+ and CX3CR1creER/+:R26tdT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
183
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 34 publications
12
183
0
3
Order By: Relevance
“…4) The time course of the PNIinduced SDH microgliosis in mice was revealed to be that microglia number increased from day 3, peaked at 1 week and declined later, which is almost similar to the temporal pattern of microgliosis reported in previous studies. 11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI). The early phase proliferation is consistent with several previous papers, 11,13) but the later phase is controversial.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…4) The time course of the PNIinduced SDH microgliosis in mice was revealed to be that microglia number increased from day 3, peaked at 1 week and declined later, which is almost similar to the temporal pattern of microgliosis reported in previous studies. 11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI). The early phase proliferation is consistent with several previous papers, 11,13) but the later phase is controversial.…”
Section: Discussionmentioning
confidence: 88%
“…11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI). The early phase proliferation is consistent with several previous papers, 11,13) but the later phase is controversial. It has previously been described that newly generated SDH microglia in response to PNI in rats continued to divide for at least 14 d after the injury.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations